2020
DOI: 10.3389/fneur.2020.614923
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic GABA Accumulation in Experimental Temporal Lobe Epilepsy

Abstract: An imbalance of excitation and inhibition has been associated with the pathophysiology of epilepsy. Loss of GABAergic interneurons and/or synaptic inhibition has been shown in various epilepsy models and in human epilepsy. Despite this loss, several studies reported preserved or increased tonic GABAA receptor-mediated currents in epilepsy, raising the question of the source of the inhibitory transmitter. We used the unilateral intracortical kainate mouse model of temporal lobe epilepsy (TLE) with hippocampal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 95 publications
1
29
1
Order By: Relevance
“…Bestrophin-1 channels are Ca 2+ activated anion channels, and increased GABA release could hence be a downstream effect of increased Ca 2+ signaling in reactive astrocytes (Lee et al, 2010). In support of this conjecture is the finding of an accumulation of GABA in reactive astrocytes in a model of mTLE (Müller et al, 2020). Potentially, this is a protective aspect of reactive astrocytes to curb epileptiform activity in this pathological tissue.…”
Section: Astrocytic Ca 2+ Signaling and Epileptogenesismentioning
confidence: 88%
“…Bestrophin-1 channels are Ca 2+ activated anion channels, and increased GABA release could hence be a downstream effect of increased Ca 2+ signaling in reactive astrocytes (Lee et al, 2010). In support of this conjecture is the finding of an accumulation of GABA in reactive astrocytes in a model of mTLE (Müller et al, 2020). Potentially, this is a protective aspect of reactive astrocytes to curb epileptiform activity in this pathological tissue.…”
Section: Astrocytic Ca 2+ Signaling and Epileptogenesismentioning
confidence: 88%
“…The major cause of epilepsy has been suggested to be a shift in the neural network of the brain toward excitation, straying away from the normally balanced excitatory-inhibitory state ( Sloviter, 1994 ; Maglóczky and Freund, 2005 ; Fritschy, 2008 ; Tóth et al, 2010 ; Huusko et al, 2015 ). This hypothesis however has previously struggled to explain the intermittent nature of epileptic seizures, that is, those experiencing epilepsy are not in a constant state of excitatory seizing ( Muller et al, 2020 ). A possible explanation for the relatively rare seizure event is a compensatory mechanism that is capable of restoring the balance of excitation–inhibition within the brain for at least a portion of time ( Walker and Kullmann, 2012 ; Pavlov and Walker, 2013 ; Staley, 2015 ).…”
Section: Selected Cellular Mechanisms Pertinent To Temporal Lobe Epilepsymentioning
confidence: 99%
“…Further, astrocyte-specific overexpression of Best1 within a Best1 KO mouse restores tonic inhibition and seizure susceptibility, strengthening the idea that astrocytic Best1 contributes to tonic inhibition by GABA release which suppresses seizure susceptibility ( Pandit et al, 2020 ). Muller et al showed a loss of hippocampal interneurons, thought to be responsible for a large portion of tonic inhibition, in a rodent model of TLE, yet interestingly found tonic inhibition levels to be the same between kainate-injected mice and control mice within the CA1 sector of the hippocampus ( Glykys and Mody, 2007 ; Muller et al, 2020 ). However, within dentate granule cells, tonic currents were found to be higher in kainate-injected mice than controls, indicating preserved as well as increased GABA levels in the epileptic hippocampus despite GABAergic interneuron loss ( Muller et al, 2020 ).…”
Section: Selected Cellular Mechanisms Pertinent To Temporal Lobe Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the understanding that the role of astrocytes goes far beyond its previously delineated supportive role in maintaining local structures and metabolism. This finding has revolutionized our understanding of epilepsy and has resulted in the concept that "astrocytic transformation" plays a major role in its pathophysiology [80].…”
Section: Two-photon Imaging In Epilepsy Researchmentioning
confidence: 99%